Deciphering the Role of p53 and TAp73 in Neuroblastoma: From Pathogenesis to Treatment - Almeida, Joana; Mota, Inês; Skoda, Jan; Sousa, Emília; Cidade, Honorina; Saraiva, Lucília (Cancers, 2022)
Neuroblastoma (NB) is an embryonic cancer that develops from neural crest stem cells, being one of the most common malignancies in children. The clinical manifestation of this disease is highly variable, ranging from spontaneous regression to increased aggressiveness, which makes it a major therapeutic challenge in pediatric oncology. The p53 family proteins p53 and TAp73 play a key role in protecting cells against genomic instability and malignant transformation. However, in NB, their activities are commonly inhibited by interacting proteins such as murine double minute (MDM)2 and MDMX, mutant p53, ΔNp73, Itch, and Aurora kinase A. The interplay between the p53/TAp73 pathway and N-MYC, a known biomarker of poor prognosis and drug resistance in NB, also proves to be decisive in the pathogenesis of this tumor. More recently, a strong crosstalk between microRNAs (miRNAs) and p53/TAp73 has been established, which has been the focused of great attention because of its potential for developing new therapeutic strategies. Collectively, this review provides an updated overview about the critical role of the p53/TAp73 pathway in the pathogenesis of NB, highlighting encouraging clues for the advance of alternative NB targeted therapies.
Keywords: neuroblastoma; p53 family proteins; targeted anticancer therapy; N-MYC; miRNAs